Surgery-induced changes in red blood cell and plasma lipid peroxidation, enzymatic and non-enzymatic antioxidants, and blood hematology of female rats: protective role of methylene blue and vitamin E - Yildiz, Hamit; Durmus, Ali Said; Simsek, Halil (Elsevier Science Bv, 2011)
Objective: The aim was to determine the effects on red blood cell (RBC) and plasma lipid peroxidation, antioxidants and blood hematology of intraperitoneally administered vitamin E (VE) and 1% methylene blue (MB) solutions for prevention of adhesions in rats. Study design: Thirty-seven female Sprague-Dawley rats were randomized into four groups. An adhesion model was constituted on the left uterine horn in three of the groups. They were then given intraperitoneally 0.9% saline (C group), 10 mg VE (VE group) and 1% MB (MB group) solutions, respectively. A sham group (Sh group), on which laparotomy was performed, received 2 ml of 0.9% saline solution. Results: In the C group, the adhesion scores were significantly higher than in the VE (p < 0.01), MB (p < 0.01) and Sh groups (p < 0.005). Results showed that adhesion formation significantly induced nitric oxide (NO) (p < 0.01) and malondialdehyde (MDA) in plasma (p < 0.01). The levels of RBC glutathione (GSH) (p < 0.05) and plasma VE (p < 0.01) significantly increased after VE administration, whereas the levels of MDA (RBC and plasma) (p < 0.01), plasma NO (p < 0.01), blood lymphocyte count (p < 0.05) and blood white blood cell (WBC) counts (p < 0.01) decreased. Treatment with MB caused a significant increase in plasma VE (p < 0.01). On the other hand, results showed that MB significantly decreased blood WBC counts (p < 0.01), plasma paraoxonase (PON1) (p < 0.001) and NO (p < 0.01), and RBC glutathione peroxidase (GPx) activity (p < 0.05) and MDA levels (p < 0.01). Conclusion: Intraperitoneal administration of MB and VE is significantly effective in preventing intraabdominal adhesion formation in a rat model. Further investigations are necessary, however, to better understand the underlying biochemical mechanisms on lipid peroxidation and antioxidants of MB. Published by Elsevier Ireland Ltd.
Keywords: Vitamin E; Methylene blue; Intraabdominal adhesions; Biochemical parameter; Rat